Economic voting behavior: The peak-end growth rule - SHEN, Zekai (Institutional Knowledge at Singapore Management University, 2024)
This paper introduces the peak-end rule to economic voting, finding that voters focus on peak and end economic growth when evaluating incumbents. Cross-national data from 595 elections in 70 countries (1960-2020) shows that the average of the highest GDP growth rate during the term and the growth rate in the election year positively impacts incumbent vote share, with peak growth having a stronger effect. Instrumental variable analysis addresses endogeneity. Heterogeneity analysis reveals that less-educated voters rely more on the peak-end rule. The findings contribute to understanding voters' behavioral patterns and improving democratic accountability.